The first Christmas - Patience, John. (Bridlington, England : Peter Haddock Ltd., 1990)
Simple text and pop-up illustrations retell the story of the birth of Jesus, from the Annunciation to the visit of the shepherds and the three kings.
Cover title.
Keywords: Jesus Christ -- Nativity -- Juvenile literature; Toy and movable books -- Specimens; Jesus Christ -- Nativity; Bible stories -- N.T.; Toy and movable books; Jesus Christ; Nativity of Jesus Christ; Toy and movable books; Juvenile works; Specimens